Barnyard millet based muffins: Physical, textural and sensory properties. Issue 1 (November 2015) - Goswami, D.; Gupta, R.K.; Mridula, D.; Sharma, M.; Tyagi, S.K.
Abstract Barnyard millet (Echinochloa frumentaceae) is an underutilized cereal, which is rich in dietary fiber and minerals, and may find potential application in bakery products such as muffins. This study investigated the effects of barnyard millet flour on muffin quality parameters by the progressive replacement of refined wheat flour (RFW) in the muffin formulations with barnyard millet (cv. VL Madira 172) flour (BMF). The pasting properties of RWF and flour blends, specific gravity of muffin batter, texture profile analysis (TPA), physical, and sensory properties of muffins were analyzed. The instrumental data indicated that the specific gravity of the batter increased while weight, baking height and hardness of muffin samples decreased with increasing proportion of BMF in flour blends. All the muffin samples, including muffins prepared from BMF only, were well accepted by the panelists during sensory evaluation. The muffins prepared from BMF only provided a comparatively higher fiber (2.1 g/100 g) and mineral content (1.75 g/100 g) than RFW muffins (0.14 g/100 g and 0.69 g/100 g, respectively). The microbiological data revealed that the quality of muffin sample was unaffected by addition of BMF during the 15 days storage period either at refrigerated or at ambient temperature.